2021
DOI: 10.24925/turjaf.v9i4.723-727.4025
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Bioactive and Textural Properties of Oleaster (Elaeagnus angustifolia L.) Fruit from Different Locations in Turkey

Abstract: The objective of this study was to evaluate the physical, bioactive and textural properties of oleaster fruits grown in different locations of Turkey. The oleaster fruits were obtained from Aksaray, Niğde and İzmir cities and their crumb and crust parts were analyzed individually and freshly. In terms of color, the crust and crumb of oleaster fruits from İzmir had the darkest color with L* values of 46.81 ± 4.06 and 78.91 ± 4.97 among all tested fruits from different locations, respectively. Total of phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Hassanzadeh and Hassanpour 43 reported the mean antioxidant capacity of the peel and pump as 74.71% and 53.76%, respectively. According to Şimşek and Sufer, 44 the crust and crumb of oleaster fruit extracts had an antioxidant activity of 6.28–14.05 μmol TE g −1 DM and 5.01–11.56 μmol TE g −1 DM, respectively. Faramarz et al 45 found that the mean antioxidant capacities (IC 50 ) of the different genotypes of E. angustifolia L. for the DPPH method were 86.95, 91.79, and 32.68 mg Trolox mL −1 for peel, flesh, and seed, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassanzadeh and Hassanpour 43 reported the mean antioxidant capacity of the peel and pump as 74.71% and 53.76%, respectively. According to Şimşek and Sufer, 44 the crust and crumb of oleaster fruit extracts had an antioxidant activity of 6.28–14.05 μmol TE g −1 DM and 5.01–11.56 μmol TE g −1 DM, respectively. Faramarz et al 45 found that the mean antioxidant capacities (IC 50 ) of the different genotypes of E. angustifolia L. for the DPPH method were 86.95, 91.79, and 32.68 mg Trolox mL −1 for peel, flesh, and seed, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the EC 50 values for O'EN-F were higher than O'EX-F, with values of 1.64 and 5.38 mg DW for free, 3.08 and 4.17 mg DW for bound, and 4.72 and 9.53 mg DW for the total antioxidant capacity, respectively. The ABTS method is used to express the Trolox equivalent antioxidant 44 the crust and crumb of oleaster fruit extracts had an antioxidant activity of 6.28-14.05 μmol TE g −1 DM and 5.01-11.56 μmol TE g −1 DM, respectively. Faramarz et al 45 found that the mean antioxidant capacities (IC 50 ) of the different genotypes of E. angustifolia L. for the DPPH method were 86.95, 91.79, and 32.68 mg Trolox mL −1 for peel, flesh, and seed, respectively.…”
Section: Chemical Nutritional and Functional Properties Of Cookiesmentioning
confidence: 99%
“…Hassanzadeh & Hassanpour (2018) reported that TFC of Elaeagnus angustifolia L. fruits peel and pulp methanolic extract in five different locations of East and West Azerbaijan provinces of Iran was in the range of 73.69 -226.5 and 94.27 -209.42 mg CAE/100 g FW, respectively. TFC of the methanolic extracts obtained from the crust and crumb of oleaster fruit varied between 5.99 ± 0.45 and 16.24 ± 1.49 mg CE/g DM, and 3.10 ± 0.01 and 6.54 ± 2.68 mg CE/g DM, respectively (Simsek & Sufer, 2021). The TFC in methanolic extracts of seed, flesh and peel of different genotype of oleaster fruit ranged from 4.7 to 17.6, 0.62 to 1.90, 0.64 to 1.13 (mM QE/mg extract), respectively (Faramarz et al, 2015).…”
Section: Total Phenolic and Flavonoid Content Of Extractsmentioning
confidence: 99%
“…TPC of oleaster fruits crust and crumb methanolic extracts grown in different locations of Turkey reported as in the range of 13.43-22.30 and 10.58-16.44 (mg GAE/g DM), respectively (Simsek & Sufer, 2021). TPC in seed, flesh and peel of different genotype of oleaster methanolic extracts ranged from 2.14 to 6.26 +-0.04, 0.14 to 1.54, and 0.12 to 2.59 (mM QE/mg extract), respectively (Faramarz et al, 2015).…”
Section: Total Phenolic and Flavonoid Content Of Extractsmentioning
confidence: 99%
See 1 more Smart Citation